Strategic Management Practices and Innovation Dynamics: Examining Their Influence on Organisational Behaviour and Customer Satisfaction in Contemporary Organizations - Devvrat (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
In an increasingly competitive and dynamic business environment, strategic management practices and innovation dynamics have emerged as critical determinants of organizational effectiveness and long-term sustainability. Contemporary organizations are required to continuously align strategic intent with innovative capabilities in order to respond effectively to changing market conditions, technological advancements, and evolving customer expectations. This study examines the influence of strategic management practices—such as strategic planning, leadership orientation, resource allocation, and performance management—on innovation dynamics, and investigates how these interactions shape organisational behaviour and customer satisfaction in modern organizational contexts. The study conceptualizes innovation dynamics as a multidimensional construct encompassing product, process, and service innovation, as well as the organization’s capacity for continuous learning and adaptation. Strategic management practices are posited to play a central role in fostering an innovation-supportive environment by encouraging employee engagement, knowledge sharing, and adaptive behaviours. Through effective strategic alignment and supportive leadership, organizations can cultivate positive organisational behaviour manifested in enhanced job satisfaction, commitment, collaboration, and innovative work behaviour. These behavioural outcomes, in turn, are expected to influence the quality of service delivery and customer experiences. From a customer-centric perspective, the study highlights that innovation driven by strategic management practices contributes to improved service quality, responsiveness, and value creation, thereby enhancing customer satisfaction. Organizations that integrate innovation into their strategic frameworks are better positioned to anticipate customer needs, personalize offerings, and maintain consistent service standards. The study also acknowledges that contextual factors such as organizational culture, leadership style, and market dynamics may moderate the relationships among strategic management practices, innovation dynamics, organisational behaviour, and customer satisfaction. This study provides an integrative perspective on the interrelationships between strategy, innovation, human behaviour, and customer outcomes. By linking strategic management practices with innovation dynamics and their behavioural and customer-level implications, the study contributes to the literature on strategic management and organizational behaviour while offering practical insights for managers seeking to enhance both internal effectiveness and customer satisfaction in contemporary organizations.
Keywords: Strategic Management Practices; Innovation Dynamics; Organisational Behaviour; Customer Satisfaction; Leadership and Strategy; Innovative Work Behaviour; Service Quality; Contemporary Organizations